2021
DOI: 10.1021/acsapm.1c00210
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle-Enhanced Three-Dimensional Boron Nitride/Reduced Graphene Oxide Skeletons for Improving Thermal Conductivity of Polymer Composites

Abstract: The thermally conductive properties of polymer composites are hugely constrained by discontinuous filler networks and high thermal contact resistances in filler/filler interfaces. Herein, a silver nanoparticle-decorated boron nitride hybrid (BN@ AgNPs) is fabricated via in situ reduction of Ag + . Subsequently, the AgNP-enhanced three-dimensional BN/reduced graphene oxide (3D-BN/rGO) skeleton with continuous structures possessing "point-plane" connections is prepared via hydrothermally treating the aqueous slu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…[7][8][9] It has been observed that polymer-based composites filled with thermally conductive fillers (e.g., carbon-based materials, [10] metal nanoparticles, [11] and ceramics particles [12] ) achieve desirable mechanical characteristics and superior TC. Hexagonal boron nitride (h-BN) nanosheets, as a promising 2D ceramic material, have several advantages over both carbon-based materials and metal nanoparticles, including high thermal stability, [13] excellent corrosion resistance, [6] outstanding oxidize resistance, [14] and excellent electrical insulation, [15] rendering it an exceptional thermal conductive filler for enhancing the heat transfer performance of polymers. [16,17] Nevertheless, the lack of active groups causes BN to clump together and distribute poorly in the polymer matrix, forming many interfacial thermal resistances (ITR) between the filler and the matrix, as well as the overlaps of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] It has been observed that polymer-based composites filled with thermally conductive fillers (e.g., carbon-based materials, [10] metal nanoparticles, [11] and ceramics particles [12] ) achieve desirable mechanical characteristics and superior TC. Hexagonal boron nitride (h-BN) nanosheets, as a promising 2D ceramic material, have several advantages over both carbon-based materials and metal nanoparticles, including high thermal stability, [13] excellent corrosion resistance, [6] outstanding oxidize resistance, [14] and excellent electrical insulation, [15] rendering it an exceptional thermal conductive filler for enhancing the heat transfer performance of polymers. [16,17] Nevertheless, the lack of active groups causes BN to clump together and distribute poorly in the polymer matrix, forming many interfacial thermal resistances (ITR) between the filler and the matrix, as well as the overlaps of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene sheets can be turned into 3D skeleton structures through an ice template, , hydrothermal reduction, , or directly chemical vapor deposition method . In these cases, composites filled with a 3D graphene skeleton still exhibit limited thermal conductivity, despite their high thermal conductivity enhancement ratios.…”
Section: Introductionmentioning
confidence: 99%
“…40% rGO addition can increase the thermal conductivity of aramid nanofibers by 1250%. Liu 35 et al added rGO to the silver nanoparticledecorated boron nitride hybrid to prepare a thermally conductive framework by hydrothermal treatment and then compounded it with PDMS to obtain a thermally conductive polymer. The thermal conductivity test results showed that the addition of rGO effectively enhanced the thermal conductivity and electrical conductivity of the composites.…”
Section: Introductionmentioning
confidence: 99%